Factor analysis of symptom profile in early onset and late onset OCD. (April 2018) - Grover, Sandeep; Sarkar, Siddharth; Gupta, Gourav; Kate, Natasha; Ghosh, Abhishek; Chakrabarti, Subho; Avasthi, Ajit
Abstract: This study aimed to assess the factor structure of early and late onset OCD. Additionally, cluster analysis was conducted in the same sample to assess the applicability of the factors. 345 participants were assessed with Yale Brown Obsessive Compulsive Scale symptom checklist. Patients were classified as early onset (onset of symptoms at age ≤ 18 years) and late onset (onset at age > 18 years) OCD depending upon the age of onset of the symptoms. Factor analysis and cluster analysis of early-onset and late-onset OCD was conducted. The study sample comprised of 91 early onset and 245 late onset OCD subjects. Males were more common in the early onset group. Differences in the frequency of phenomenology related to contamination related, checking, repeating, counting and ordering/arranging compulsions were present across the early and late onset groups. Factor analysis of YBOCS revealed a 3 factor solution for both the groups, which largely concurred with each other. These factors were named as hoarding and symmetry (factor-1), contamination (factor-2) and aggressive, sexual and religious factor (factor-3). To conclude this study shows that factor structure of symptoms of OCD seems to be similar between early-onset and late-onset OCD. Highlights: Subjects with early onset (≤18 years) and late onset (>18 years) did not differ in terms of obsessions. Checking, counting and repeating compulsions were more common in the early onset group. Contamination related compulsions were more commonly seen in the late onset group. Factor analysis of YBOCS in both the groups yielded 3 factor solution.